2020
DOI: 10.3390/nu12061639
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Mechanisms by which Heat Stress Potentially Induces Kidney Inflammation and Chronic Kidney Disease in Sugarcane Workers

Abstract: Background: Chronic kidney disease of non-traditional origin (CKDnt) is common among Mesoamerican sugarcane workers. Recurrent heat stress and dehydration is a leading hypothesis. Evidence indicate a key role of inflammation. Methods: Starting in sports and heat pathophysiology literature, we develop a theoretical framework of how strenuous work in heat could induce kidney inflammation. We describe the release of pro-inflammatory substances from a leaky gut and/or injured muscle, alone or in combination with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 117 publications
(213 reference statements)
4
64
1
5
Order By: Relevance
“…Scand J Work Environ Health -online first Dysuria, heat events, and muscle events in sugarcane workers Among sugarcane workers, cane cutters appear at greatest risk of MeN (6,(9)(10)(11)(12). One of the main proposed causal hypotheses has focused on the potential physical challenges faced by cane cutters, including strenuous physical exertion in extreme heat (3,(13)(14)(15)(16)(17)(18), such that volume depletion in conjunction with other factors, such as muscle injury, results in recurrent episodes of subclinical kidney injury that eventually manifest with clinically apparent CKD (13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Scand J Work Environ Health -online first Dysuria, heat events, and muscle events in sugarcane workers Among sugarcane workers, cane cutters appear at greatest risk of MeN (6,(9)(10)(11)(12). One of the main proposed causal hypotheses has focused on the potential physical challenges faced by cane cutters, including strenuous physical exertion in extreme heat (3,(13)(14)(15)(16)(17)(18), such that volume depletion in conjunction with other factors, such as muscle injury, results in recurrent episodes of subclinical kidney injury that eventually manifest with clinically apparent CKD (13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…With demanding physical exertion, cane cutters may also be at risk of muscle damage with release of nephrotoxic proteins from muscle, including myoglobin (13,14,(17)(18)(19)(24)(25)(26). Elevated concentrations of muscle injury biomarkers, myoglobin and creatinine kinase (CK), are associated with muscle damage-related illness and acute kidney injury (AKI) (24)(25)(26)(27).…”
mentioning
confidence: 99%
“…Studies have shown biochemical evidence of heatinduced kidney injury. 23,24,27,59 which can be induced with increases in serum and urine uric acid and extracellular volume depletion. 53 In addition, rest breaks were found to be protective against severe increases in creatinine and a nonsignificant trend that increasing USG was associated with increases in creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the impact of hypohydration on aspects of worker health beyond the workplace has begun to be elucidated. For instance, repeated exposure to a hypohydrated state caused by severe physical work in the heat has been proposed to bring about chronic kidney disease, which is speculated to be due to the workers experiencing repeated bouts of subclinical kidney injury (Glaser et al., 2016 ; Hansson et al., 2020 ; Johnson et al., 2019 ; Mix et al., 2018 ; Nerbass et al., 2017 , 2019 ; X. Yang et al., 2020 ). Cases of chronic kidney disease have been reported in workers performing manual work in hot environments in hottest regions in the world (Aguilar & Madero, 2019 ; Butler‐Dawson et al., 2019 ; Glaser et al., 2016 ; X. Yang et al., 2020 ).…”
Section: Narrative Reviewmentioning
confidence: 99%